Mount Logan ice core record of tropical and solar influences on Aleutian Low variability: 500–1998 A.D. Issue 19 (10th October 2014) - Osterberg, Erich C.; Mayewski, Paul A.; Fisher, David A.; Kreutz, Karl J.; Maasch, Kirk A.; Sneed, Sharon B.; Kelsey, Eric
Abstract: Continuous, high‐resolution paleoclimate records from the North Pacific region spanning the past 1500 years are rare; and the behavior of the Aleutian Low (ALow) pressure center, the dominant climatological feature in the Gulf of Alaska, remains poorly constrained. Here we present a continuous, 1500 year long, calibrated proxy record for the strength of the wintertime (December–March) ALow from the Mount Logan summit (PR Col; 5200 m asl) ice core soluble sodium time series. We show that ice core sodium concentrations are statistically correlated with North Pacific sea level pressure and zonal wind speed. Our ALow proxy record reveals a weak ALow from circa 900–1300 A.D. and 1575–1675 A.D., and a comparatively stronger ALow from circa 500–900 A.D., 1300–1575 A.D., and 1675 A.D. to present. The Mount Logan ALow proxy record shows strong similarities with tropical paleoclimate proxy records sensitive to the El Niño–Southern Oscillation and is consistent with the hypothesis that the Medieval Climate Anomaly was characterized by more persistent La Niña‐like conditions while the Little Ice Age was characterized by at least two intervals of more persistent El Niño‐like conditions. The Mount Logan ALow proxy record is significantly ( p < 0.05) correlated and coherent with solar irradiance proxy records over various time scales, with stronger solar irradiance generally associated with a weaker ALow and La Niña‐like tropical conditions. However, a step‐like increase in ALow strength during the Dalton solar minimum circa 1820 is associated with enhanced Walker circulation. Furthermore, rising CO2 forcing or internal variability may be masking the twentieth century rise in solar irradiance. Key Points: We have developed a 1500 year continuous ice core record of the Aleutian Low The Medieval Climate Anomaly (Little Ice Age) had a weaker (stronger) ALow Our record indicates strong tropical‐extratropical coupling and solar forcing